51.7k views
4 votes
Describe how to transform the graph of f(x) = x² to obtain

the graph of the related function g(x) = f(–4x – 3)) + 1.
Then draw the graph of g(x).

User Avellable
by
5.4k points

1 Answer

3 votes

Answer:

The functions given are:

f(x) = x²

g(x) = f(-4x-3) + 1

First, find f(-4x-3):

f(x) = x²

f(-4x-3) = (-4x-3)²

Find g(x):

g(x) = f(-4x-3) + 1

g(x) = (-4x-3)² + 1

g(x) = (-1)² (4x+3)² + 1

g(x) = (4x+3)² + 1

First take

y = (x)²

Compress the graph along x axis by multiplying x with 4

y = (4x)²

Shift the graph left by 0.75 units, by adding 3 to x term.

y = (4x+3)²

Shift the graph up by 1 unit by adding 1 to the total terms.

y = (4x+3)² +1

Describe how to transform the graph of f(x) = x² to obtain the graph of the related-example-1
User Brad T
by
5.8k points